Ineptitude, ignorance, or intent: The social construction of failure in development. (June 2018) - Venugopal, Rajesh
Highlights: Examines how development is often characterised as a failure. Explains that failure is socially constructed. Outlines three categories of failure: implementation, design, agenda. Abstract: This paper explores the social construction of failure in development policy and academic narratives. Talk of failure is commonplace in development, and this paper seeks to use that as a heuristic to understand what that it signifies beyond face value. Drawing on a wide range of primary and secondary texts to provide illustrative evidence, the paper explores how failure is constructed, and advances a three-fold typology of failures that vary in terms of their positionality, the critical variables they identify as responsible, their epistemological stance, and the importance they accord to politics.